PENERAPAN METODE PREVIEW, QUESTION, READ, REFLECT, RECITE, REVIEW (PQ4R) BERBANTUAN MEDIA POP UP BOOK UNTUK MENINGKATKAN LITERASI MEMBACA SISW KELAS V UPTD SD NEGERI 49 PAREPARE (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The problem in research is low reading literacy in fifth grade students of UPTD SD Negeri 49 Parepare. This research aims to improve the learning process of reading literacy in fifth grade students of UPTD SD Negeri 49 Parepare. This research uses a qualitative approach with the type off classroom action research. The subjects in this research is a teacher and fourth grade students of  UPTD SD Negeri 49 Parepare with a total of 20 students in the consisting of thirteen men and seven women. The focus in this study is the focus of the process and the focus of the research results with the implementation of the PQ4R method The data collection techniques in this study are observation, tests, and documentation. The data analysis techniques in this study are data condensation, data presentation, and conclusion drawn. The results of the research from cycle I and cycle II show that in cycle I teacher teaching activities can be categorized as sufficient (C), observation of student learning activities in the category of less (C). In cycle II,  process teaching activities can be categorized as good (B), student learning activities in the good category (B) The application of the PQ4R method can improve the reading literacy of grade students of UPTD SD Negeri 49 Parepare.